-67=-32n+29

Simple and best practice solution for -67=-32n+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -67=-32n+29 equation:


Simplifying
-67 = -32n + 29

Reorder the terms:
-67 = 29 + -32n

Solving
-67 = 29 + -32n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '32n' to each side of the equation.
-67 + 32n = 29 + -32n + 32n

Combine like terms: -32n + 32n = 0
-67 + 32n = 29 + 0
-67 + 32n = 29

Add '67' to each side of the equation.
-67 + 67 + 32n = 29 + 67

Combine like terms: -67 + 67 = 0
0 + 32n = 29 + 67
32n = 29 + 67

Combine like terms: 29 + 67 = 96
32n = 96

Divide each side by '32'.
n = 3

Simplifying
n = 3

See similar equations:

| 20(b+7)=-20 | | 5b-16=39 | | 76=y/4 | | 2.1x+1.3=-9.2 | | 8.5x-6.5=6.8x+10.0 | | 6(v+3)-2v=2(2v+1)-11 | | 12x-3(3x-6)=2x+2 | | 25=13+8d | | 240=170+5d | | 10f+5= | | -3(l+4)-l-3=-4(l+5)+5 | | 0.8x-0.4(60+x)=0.067(60) | | 0.18y+0.03(y+6000)=810 | | (2x+2)=-4 | | 16x^7-x^3-65= | | 3/4÷2= | | 6(2/3-3) | | 14x-2(2x-4)=9x+9 | | 4x^4+12x^7=0 | | X+100=-235 | | 8.3x+5=9.7x-1 | | 121x^2-324= | | -9/-3*2/-5*8 | | x+x-28=152 | | -5/6t=15 | | y=2x^2+12x-39 | | 9a^3-5a^3= | | (x^4-25)(x^2-1)=0 | | 0.05*(x^90)=5 | | 12x+3=18x-3 | | 27w/-12w | | 4(m+4)+8(-12m+11)=m-8+8m+11 |

Equations solver categories